A mini-invasive technique for severe arthrofibrosis of the knee: A technical note. Issue 8 (August 2016) - Shang, Ping; Liu, Hai-xiao; Zhang, Yu; Xue, En-xing; Pan, Xiao-yun
Abstract: Purpose: In this article, a mini-invasive technique is described, which consists of arthroscopic adhesiolysis and quadriceps pie-crusting lengthening basing on pre-operative sonographic examination. Sonographic diagnostic value of quadriceps tendon fibrosis is also evaluated. Methods: Pre-operative sonographic examination was performed to make an accurate location diagnosis of quadriceps fibrosis. After arthroscopic adhesiolysis, percutaneous pie-crusting release was performed basing on preoperative sonographic examination. An 18-gauge needle was used to puncture the stiff fibrous band of the distal and lateral quadriceps tendon under maximum knee flexion. The contractural quadriceps tendon is gradually released after 60–100 needle punctures. Results: This technique was performed in five post-traumatic stiff knees and three stiff knees after previous infection. The contractural rectus femoris tendon is average 22% thinner than contralateral parts according to sonographic measurement. Mean maximum flexion increased from 35° preoperatively to 80° after arthroscopic adhesiolysis and 120° after pie-crusting. Conclusions: This technique is a simple, effective and mini-invasive method, allowing an immediate, aggressive rehabilitation postoperatively. Pre-operative sonographic location of quadriceps tendon fibrosis could potentially improve the efficacy and accuracy of percutaneous pie-crusting procedures.